The effects of advertising models for age‐restricted products and self‐concept discrepancy on advertising outcomes among young adolescents - Pezzuti, Todd; Pirouz, Dante; Pechmann, Cornelia (Journal of Consumer Psychology, 2015)
AbstractResearch on discrepancies between the actual self and ideal self has examined self‐discrepancies in knowledge, skills and stature but age‐based self‐discrepancies have only recently received attention and so we studied this phenomenon in young adolescents. In three studies we identified a product‐category contextual cue that apparently caused adolescents to respond to an existing age‐based self‐discrepancy. Specifically we found that when the contextual cue was advertising for an age‐restricted product, adolescents conformed to dissimilar young adult advertising models and diverged from similar adolescent models. This indicated that the contextual cue caused them to respond to an age‐based self‐discrepancy and use a product associated with the ideal self rather than the actual self. Importantly, this response was stronger among adolescents that were more dissatisfied with their age. With advertising for an age‐unrestricted product, adolescents conformed to adolescent advertising models and diverged from young adult models. Industry policies for age‐restricted products assume that similarity drives influence and therefore mandate that advertising models be young adults rather than adolescents. Our findings suggest this assumption is invalid for age‐restricted products.